Usaha Perkuatan Pondasi Rumah Untuk Tanah Rawa di Banjarmasin - Nursyarif Agusniansyah; Gusti Novi Sarbini (Universitas Islam Raden Rahmat, Malang, 2024)
For the condition of building houses in swampland is to use stilt house construction. Building houses using rows of wooden pillar is above the condition of watery soil. This row of wooden pillar as a support for the load of the building above it and channeled through the foundation. While the foundation is used to overcome the condition of very low soil carrying capacity, galam wood is used which is able to strengthen the carrying capacity of the soil. This galam pile foundation has friction or adhesion properties with a certain carrying capacity. In addition to wooden pillar, new materials are also used in the form of pillar and concrete plates foundations.. The discovery of field foundation development is to combine the use of wooden pillar with concrete column.